Predictive Value of Lactate/Albumin Ratio for Death and Multiple Organ Dysfunction Syndrome in Patients with Sepsis: Predicting Death and Multiple Organ Dysfunction Syndrome Using Lactate/Albumin Ratio - Huang, Shuwei (Journal of Medical Biochemistry, 2024)
Introduction: Multiple organ dysfunction syndrome (MODS) is common after sepsis and increases mortality. Lactate (Lac) can assess the prognosis of patients. Albumin (Alb) is closely associated with inflammatory response in sepsis patients. This work evaluated the predictive value of Lac/Alb for prognosis of sepsis patients. Materials and Methods: data of 160 sepsis patients were retrospectively collected. Lac and Alb levels were measured upon admission, at 24 hours and 48 hours later. Using 0.45 as the cutoff value for Lac/Alb, patients were rolled into high-level (HL) and low-level (LL) groups. MODS rates and mortality rates were analyzed. Receiver operating characteristic (ROC) curves were utilized to evaluate the predictive value of 48-hour Lac/Alb for patient prognosis. Correlation between Lac/Alb and APACHE II and SOFA scores was assessed. Results: the 12-month follow-up revealed 52 deaths (32.5%), and MODS occurred in 49 cases (30.6%) on the 7th day. The MODS group possessed elevated Lac and Lac/Alb and decreased Alb to the N-MODS group (P
Keywords: Sepsis; Multiple organ dysfunction syndrome; Mortality; Lactate; Low albumin